Bilingualism and cognition: analysis of executive function performance in bilingual and monolingual professors and teachers from institutions in Pereira (2021)
This quasi-experimental research sought to determine through a quantitative study if there was an EF advantage in socio-demographically matched bilingual professors relative to their monolingual counterparts, and if there was a mediation or confounding effect on EFs due to the role of SES (socioeconomic status). The data was collected using two tests and one task to quantify each element of the tripartite of the EFs, those materials are: 1) the Stroop test to measure the inhibition component, 2) task switching to measure the shifting component, and 3) the Corsi block-tapping task to measure the updating component. These were used to assess the EF outcomes on bilingual and monolingual professors and teachers from institutions in Pereira. They were filtered beforehand with the help of a sociodemographic language questionnaire to match them as much as possible in terms of their background, so that more accurate results could be gathered, and therefore contribute to the current state of the art. There were two hypotheses that this paper sought to determine experimentally 1) there is a bilingual advantage regarding on of the aspects in the EFs tripartite (inhibition, shifting, or updating), 2) there is a bilingual advantage in the executive function performance as a whole, instead of benefiting just one component, or 3) both groups obtain similar results in the overall of the different tasks and test in the tripartite of the EFs. The contri bution of this paper will be useful to widen the current state of the art in this field in the Colombian context, and it will also help to build a stronger foundation by shedding light on the issue about knowing whether bilingualism affects or not the executive function performance.